MassARRAY multigene screening combined with LDL-C and sdLDL-C detection for more favorable outcomes in type 2 diabetes mellitus therapy - Yong Tian; Junhong Wang; Yanxiao Liu; Xiangguang Luo; Ziying Yao; Xinjun Wang; Yuanyuan Zhang; Cheng Xu; Xiaoyu Zhao (BMC, 2021)
Abstract Background To determine the clinical value of multigene polymorphisms, LDL-C and sdLDL-C on T2DM therapy. Methods In total, 352 T2DM patients before and after treatment and 48 healthy individuals were enrolled in this study. LDL-C and sdLDL-C were detected in 352 T2DM patients and 48 healthy individuals by Quantimetrix Lipoprint System. The 11 gene polymorphisms-HTR3B (rs2276307, A > G), APOE (rs7412, c.526C > T), APOE (rs429358, c.388 T > C), CYP2C9*3 (rs1057910, c.1075A > C), KIF6 (rs20455, c.2155 T > C), HMGCR (rs17238540, T > G), HMGCR (rs17244841, A > T), ABCB1 (rs2032582, A > C/T), HTR7 (rs1935349, C > T), SLCO1B1 (rs4149056, c.521 T > C), and CETP (rs708272, G > A)-were screened in these 352 T2DM patients by the Agena Bioscience MassARRAY system before therapy. Results Genetic polymorphisms associated with T2DM and statin effects in pretreatment patients were detected, then results showed that all 11 genes had heterozygous mutation, and 7 genes had homozygous mutation in 352 T2DM patients, more specifically reflected that these gene polymorphisms were common in Chinese T2DM patients. LDL-C and sdLDL-C were detected before and after treatment, sdLDL mainly existed in T2DM patients, and T2DM patients had higher mean levels of sdLDL-C than healthy people. After pharmacotherapy, the coincidence rates of decreases in LDL-C and sdLDL-C levels were 88.35% (311/352) and 84.09% (296/352), consistent with patients in remission. Conclusions Gene polymorphisms related to pharmacotherapy were common in Chinese T2DM patients. And the expression of LDL-C and sdLDL-C was consistent with the T2DM disease course. Combined multigene screening before therapy and LDL-C and sdLDL-C detection before and after therapy could better assist T2DM treatment.